The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1063/1.2956598
|View full text |Cite
|
Sign up to set email alerts
|

Structural transformation in antiferroelectric PbZrO3-relaxor ferroelectric Pb(Ni1∕3Nb2∕3)O3 solid solution system

Abstract: The solid solution between the antiferroelectric (AFE) PbZrO3 (PZ) and the relaxor ferroelectric (FE) Pb(Ni1∕3Nb2∕3)O3 (PNN) was synthesized by the columbite precursor method. The crystal structure, phase transformations, and dielectric and thermal properties of (1−x)PZ-xPNN where x=0.00–0.30 were investigated. With these data, the FE phase diagram between PZ and PNN has been established. The crystal structure data obtained from X-ray diffraction indicate that the solid solution PZ-PNN, where x=0.00–0.30, succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…Choi et al [22] reported that in the Bi(Ni 1/2 Ti 1/2 )O 3 -PbTiO 3 (BNiT-PT), the tricritical point in the solid solution also corresponded closely to t ∼ 1.0. Similar phenomena have been observed in the Bi(Mg 3/4 W 1/4 )O 3 -PbTiO 3 (BMW-PT) system by Stringer et al [23] and our previous work on PbZrO 3 related materials [24,25].…”
Section: Resultssupporting
confidence: 61%
“…Choi et al [22] reported that in the Bi(Ni 1/2 Ti 1/2 )O 3 -PbTiO 3 (BNiT-PT), the tricritical point in the solid solution also corresponded closely to t ∼ 1.0. Similar phenomena have been observed in the Bi(Mg 3/4 W 1/4 )O 3 -PbTiO 3 (BMW-PT) system by Stringer et al [23] and our previous work on PbZrO 3 related materials [24,25].…”
Section: Resultssupporting
confidence: 61%
“…[8,10] or (Pb,Ba)ZrO 3 [5,7]. Nevertheless, at high temperature, the dielectric data revealed an enhanced dielectric loss with increasing BAO concentration.…”
Section: Dielectric Propertiesmentioning
confidence: 71%
“…The FE intermediate phase can be induced by adding Ba 2+ , Sr 2+ , and La 3+ at the Pb 2+ -site [2,[4][5][6][7]. Moreover, our recent research found that the FE intermediate phase also can be induced by adding, for example, hybrid-doped Ni 2+ /Nb 5+ , Zn 2+ /Nb 5+ , Co 2+ /Nb 5+ and Mg 2+ /W 6+ at the Zr 4+ -site [8][9][10][11][12][13][14]. BiMO 3 ; M = Fe 3+ , Mn 3+ and Nd 3+ has received a lot of attention recently as a multiferroic, and investigation of the solid solutions, BiMO 3 -PbTiO 3, has shown that they improve ferroelectric properties of PbTiO 3 , reduce the amount of lead, and find new morphotropic phase boundary piezoelectrics [15][16][17][18].…”
Section: Introductionmentioning
confidence: 94%
“…Recently, our research work reported that the intermediate phase can also be introduced by partial replacement of Zr 4+ ions with complex B-site ions such as Ni 2+ /Nb 5+ [23,24], Zn 2+ /Nb 5+ [25], or Co 2+ /Nb 5+ [26]. Furthermore, our previous study found that by adding minor amounts (2-10 mol%) of antiferroelectric Pb(Mg 1/2 W 1/2 )O 3 (PMW) into antiferroelectric PZ, the temperature range expanded to an intermediate phase, which was characterized by evident frequency dispersion in dielectric permittivity [27].…”
Section: Introductionmentioning
confidence: 99%